Characteristics and outcomes of patients with psoriasis treated with apremilast in the real-world in Austria - results the APPRECIATE study - Constanze Jonak; Isolde Göttfried; Sylvia Perl-Convalexius; Barbara Gruber; Martina Schütz-Bergmayr; Igor Vujic; Wolfgang Weger; Nikolaus Schicher; Lydia Semlin; Margit Hemetsberger; Myriam Cordey; Paul Sator (SAGE Publishing, 2023)
Background: Apremilast, an oral phosphodiesterase 4 inhibitor, is approved in the European Union for the treatment of moderate-to-severe chronic plaque psoriasis in adult patients refractory or contraindicated to or intolerant of other systemic therapies. Objectives: The APPRECIATE study assessed apremilast use in real-world practice and its clinical value to physicians and patients. APPRECIATE was a multinational, observational, retrospective, cross-sectional study. Methods: Apremilast effectiveness at 6 (±1) months was assessed on the basis of psoriasis severity and health-related quality-of-life scores and treatment satisfaction using physician/patient-reported outcomes, respectively. We report the Austrian cohort of 72 patients. Results: At 6 (±1) months, three-quarters of patients remained on apremilast, while physicians and patients reported treatment benefits across all psoriasis symptoms and manifestations. Of patients, the majority were satisfied with their treatment and achieved treatment goals considered most relevant. Patients' and physicians' perceptions of treatment effectiveness were aligned, and health-related quality-of-life scores indicated an improvement in the majority of patients. Apremilast tolerability was consistent with the known safety profile. Conclusions: Among psoriasis patients receiving apremilast in Austria, improvement in clinical outcomes were observed and satisfaction with apremilast treatment among patients and physicians was high. Registration: ClinicalTrials.gov NCT02740218